2020
DOI: 10.3390/cells9071736
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 Inhibition and CRISPR-Cas9 Knockout Reduce Inflammation Induced by Hyperphysiological Stretching in Human Annulus Fibrosus Cells

Abstract: Mechanical loading and inflammation interact to cause degenerative disc disease and low back pain (LBP). However, the underlying mechanosensing and mechanotransductive pathways are poorly understood. This results in untargeted pharmacological treatments that do not take the mechanical aspect of LBP into account. We investigated the role of the mechanosensitive ion channel TRPV4 in stretch-induced inflammation in human annulus fibrosus (AF) cells. The cells were cyclically stretched to 20% hyperphysiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…They respond to these loads via a number of mechanotransduction mechanisms, which have been reviewed previously [ 130 , 131 , 132 ]. For example, TRP channels, whereby TRPV4 as well as TRPC6, TRPM2, and TRPML1 stand out due to fundamental roles in osmo- and mechano-sensing [ 118 , 133 , 134 ]. NP cells are more responsive to hydrostatic pressure, while AF cells respond better to cyclic strain [ 135 ].…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%
See 2 more Smart Citations
“…They respond to these loads via a number of mechanotransduction mechanisms, which have been reviewed previously [ 130 , 131 , 132 ]. For example, TRP channels, whereby TRPV4 as well as TRPC6, TRPM2, and TRPML1 stand out due to fundamental roles in osmo- and mechano-sensing [ 118 , 133 , 134 ]. NP cells are more responsive to hydrostatic pressure, while AF cells respond better to cyclic strain [ 135 ].…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%
“…The p38 signaling pathway is generally activated by stressors and is known to regulate inflammation, autophagy, apoptosis, and differentiation [ 241 ]. Numerous studies have investigated p38 in the IVD, thereby identifying hypoxia [ 245 ], hyperosmolarity [ 120 ], hyperphysiological mechanical loads [ 133 ], ER stress [ 258 ], acidity [ 257 ], high glucose levels [ 256 ], and IL-1 [ 253 ] as potent activators. Interestingly, p38 is connected to TPRV4 [ 133 ], which has previously been described to transduce mechanical, inflammatory, and pain signals in cartilage [ 259 ].…”
Section: Ivd Regeneration Strategies: Biological Targets and Biomamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Cambria et al [ 79 ] reported that the transient receptor potential vanilloid type 4 (TRPV4) gene was successfully knocked out in vitro by the CRISPR/Cas9 gene-editing system in AF-injured patients with chronic LBP. By using CRISPR, they investigated the role of the TNFR4 gene in the regulation of IL6 and IL8 using CRISPR and the reduction in inflammation induced by hyper physiological stretching of AF cells.…”
Section: Gene Therapymentioning
confidence: 99%
“…The TRP super‐family is composed of six sub‐families in mammals: TRPC (canonical), TRPV (vanilloid), TRPM (melastatin), TRPP (polycystin), TRPML (mucolipin), and TRPA (ankyrin) 19 . Several studies have recently investigated the expression and function of TRP channels in the IVD 20‐24 . The mechanosensitive member 4 of the vanilloid subfamily (TRPV4) is especially intriguing for the study of load‐mediated IVD degeneration and LBP.…”
Section: Introductionmentioning
confidence: 99%